Four Comedies by Pedro Calderón de la Barca - Calderón de la Barca, Pedro, 1600-1681 (Book collections on Project MUSE., 1980)
Calderón, the great dramatist of Spain's Golden Age, was a skilled writer of comedy. His serious dramas have long been highly regarded in the English-speaking world, but his many sparkling comedies are an untapped reservoir for the contemporary theater. The four plays in this volume, three of which appear in English for the first time, have been translated by Kenneth Muir, the noted British scholar and director. These are comedies of intrigue. They turn on mysterious, quarrels, and jealousies, and they abound in complication and misunderstandings, yet in the end all is explained, to the delight.